American biodefense how dangerous ideas about biological weapons shape national security - Smith, Frank L. (Cornell studies in security affairs, 2014)
Biological weapons have threatened US national security since at least World War II. Historically, however, the US military has neglected research, development, acquisition, and doctrine for biodefense. Given the ideas at work inside the US military, Smith explains how the lessons learned from biodefense can help solve other important problems that range from radiation weapons to cyber attacks.